Deferasirox-induced hyperammonemia and Fanconi syndrome: a case report - Zhou, Houfu; Xiong, Daoxue; Feng, Yan; Jiang, Jianyu (Frontiers in Pediatrics, 2024)
Background The exact mechanism of hyperammonemia is thought to be multifactorial, but is not yet fully understood. No studies have yet reported hyperammonemia combined with Fanconi syndrome caused by deferasirox. Case presentation A 10-year-old girl was admitted for vomiting and altered consciousness. Blood testing revealed hyperammonemia and normal liver and coagulation functions. During hospitalization, the patient also exhibited hyperchloremic metabolic acidosis, hypokalemia, hyponatremia, and hypophosphatemia. Additionally, urinalysis revealed glucose and protein levels clinically consistent with Fanconi syndrome. The patient had a history of severe beta-thalassemia and had received intermittent blood transfusions for approximately ten years. The patient had been administered oral deferasirox at a 400 mg/day dose at the age of four, which had been gradually increased to the current 750 mg/day dosage. Upon admission, deferasirox was discontinued and treatment including mechanical ventilation, continuous blood purification therapy for ammonia reduction and acidosis, and electrolyte imbalance corrections was administered. Subsequently, serological markers returned to normal, urine test findings improved. To the best of our knowledge, this is the first report of a case of hyperammonemia with Fanconi syndrome owing to deferasirox. Conclusions For effective management and long-term follow-up of chronic diseases in children, pediatricians must master standardized treatments and the adverse reactions of various drugs. When symptoms are difficult to explain clinically, we must trace the source and adjust the treatment plan to maximize improving the patient's prognosis.